Bibliometric Analysis: Lecturers' Research Performance - Silalahi, Rudi Yanto Batara; Moeins, Anoesyirwan; Marhalinda (IJHCM (International Journal of Human Capital Management), 2024)
The research performance of lecturers is very important for several reasons, both in terms of the development of higher education institutions and the broader contributions to society and scientific knowledge. This study aims to identify research trends related to lecturers' research performance from 2019 to 2024. To achieve this goal, a literature review method was used, employing bibliometric analysis with VOSviewer software. In this study, the applied method is a quantitative approach using bibliometric analysis. As a data source, 644 scientific publications from the ScienceDirect database were used, selected through a search with the keyword "lecturers' research performance." The results of this study indicate that the trends in lecturers' research performance encompass topics such as higher education, artificial intelligence, education, academic performance, teacher education, Covid-19, sustainability, and motivation. Therefore, future research is suggested to investigate keywords such as gender, employability, formative assessment, self-efficacy, and collaboration.